Abordaje fisioterapéutico en tendinopatía del manguito rotador en pacientes que acuden al área de terapia física del Hospital General Martín Icaza, Babahoyo. Noviembre 2023 - abril 2024. - Chang Riquero, Meily Alexandra (2024)
Tendinopathy refers to injuries in which there is no tissue breakdown and causes pain and disability. Rotator cuff tendinopathy is a highly prevalent pathology in primary care that produces significant deteriorations in quality of life and whose treatment represents a challenge for health professionals. This research aimed to describe the physiotherapy approach applied in patients with rotator cuff tendinopathy. This study was carried out in the physical therapy and rehabilitation area of the Martin Icaza General Hospital with 57 patients from 30 to 65 years. A mixed methodology was used, as an interview with the 2 physical therapists responsible for the area was conducted, additionally to performing a survey of the patients to collect qualitative information that was analyzed through graphs. The results showed that a combination of physical agents such as electrotherapy, cryotherapy, and thermotherapy with therapeutic exercise initially of isometric type progressing to isotonic exercise has beneficial outcomes in the treatment of this pathology, producing pain reduction and improving functionality.